1979
DOI: 10.1148/133.2.507
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Computed Tomography and Intracranial Pressure Monitoring in Acute Head Trauma Patients

Abstract: A preliminary retrospective correlation between computed tomographic scans and intracranial pressure (ICP) monitored was performed for 21 patients. No patient with a normal CT scan had elevated ICP. The lowest correlation was noted with slit ventricles; the highest, with dilatation of the contralateral temporal horn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…In adult patients with normal initial CT scans, studies have shown conflicting results with regard to patients who later develop elevated ICP, as shown in Table 1 [6,7,[12][13][14]. It remains to be determined whether a normal initial CT scan can be used to predict later ICP.…”
Section: Radiologic Findingsmentioning
confidence: 99%
“…In adult patients with normal initial CT scans, studies have shown conflicting results with regard to patients who later develop elevated ICP, as shown in Table 1 [6,7,[12][13][14]. It remains to be determined whether a normal initial CT scan can be used to predict later ICP.…”
Section: Radiologic Findingsmentioning
confidence: 99%
“…Status of the peripheral sulci -In their study, Sadhu et al 8 found no correlation between the status of the peripheral sulci and ICP. In this series, all patients who were operated on had effaced sulci, at least on the side of the lesion.…”
Section: Status Of the Suprasellar And Ambient Cisterns -mentioning
confidence: 82%
“…Gailbraith and Te a s d a l e 7 detected no diff e rence in midline shift between the patients who were operated on and those who received conservative treatment. Sadhu et al 8 and Tabaddor et al 9 found no corre l ation between midline shift and ICP status. On the other hand, Marshall et al…”
Section: Position Of the Midline Structures And Status Of The Csf-filmentioning
confidence: 94%
See 2 more Smart Citations